2022
DOI: 10.1021/acs.iecr.2c01443
|View full text |Cite
|
Sign up to set email alerts
|

Zickzack Packings for Deaeration in Rotating Packed Beds─Improved Rotor Design to Counter Bypass Flows

Abstract: Recently, various internals for rotating packed beds (RPBs) have been developed. However, the technical maturity of these internals is still relatively low compared to packings for columns. In this work, a novel design is proposed for RPBs, consisting of a seal structure combined with a Zickzack packing. The seal structure around the packing was developed to avoid bypasses in the spaces between packing and inner rotor walls, comparable to wall wipers used for structured packings in columns. This design was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Figure ). This observation supports the often mentioned argument for different types of rotors, including ZZ packings and RZBs, that the liquid holdup inside the rotor increases with increasing fluid load. Furthermore, the difference between the liquid fractions at the upper and lower baffles increases with decreasing n rot for all radii.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure ). This observation supports the often mentioned argument for different types of rotors, including ZZ packings and RZBs, that the liquid holdup inside the rotor increases with increasing fluid load. Furthermore, the difference between the liquid fractions at the upper and lower baffles increases with decreasing n rot for all radii.…”
Section: Resultssupporting
confidence: 90%
“…The total wet pressure drop Δ p in the RPB equipped with unstacked ZZ packing is shown in Figure . As previously observed by Loll et al, a pressure drop minimum can be observed, and the value of the minimum as well as the n rot at which this minimum occurs ( n pmin ) depends on the fluid rates. At a gas flow rate of V̇ G,1 = 0.5 m 3 h –1 and a liquid flow rate of V̇ L,1 = 0.48 m 3 h –1 , Δ p increased monotonically with n rot for n rot > 500 rpm.…”
Section: Resultssupporting
confidence: 74%
“…Moreover, the uniform radial separation profile will help scale up the packing from lab to industrial scale effectively. The slight dip in the radial separation profile for 300 rpm in Figure might be due to liquid bypass through the holes or spaces in the ZZ packing . Overall, ZZ packing showed promising results by improving the liquid distribution and holdup.…”
Section: Resultsmentioning
confidence: 96%
“…13−15 In a high-gravity device called "chemical industry transistor", 16 liquid is cut into a liquid droplet, liquid filament, and liquid film by rotating packing, and a huge and rapidly updating phase boundary area is formed to greatly strengthen the micromixing and mass transfer. 15,17 As a typical high-gravity device, the impinging stream-rotating packed bed (IS-RPB) developed by the Shanxi Province Key Laboratory of Higee-Oriented Chemical Engineering, North University of China, has been widely used in the reaction process of liquid−liquid precipitation. 18−20 The micromixing effect is great due to the existence of high dispersion and strong mixed packing area, and the segregation index representing the mixing effect of the IS-RPB is only 0.003−0.018 as evaluated by the iodide−iodate system.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of process intensification technology, high-gravity technology can improve the process safety through continuous production. Specially, the centrifugal force field generated by the high-speed rotating packing is used to simulate the high-gravity field. In a high-gravity device called “chemical industry transistor”, liquid is cut into a liquid droplet, liquid filament, and liquid film by rotating packing, and a huge and rapidly updating phase boundary area is formed to greatly strengthen the micromixing and mass transfer. , As a typical high-gravity device, the impinging stream-rotating packed bed (IS-RPB) developed by the Shanxi Province Key Laboratory of Higee-Oriented Chemical Engineering, North University of China, has been widely used in the reaction process of liquid–liquid precipitation. The micromixing effect is great due to the existence of high dispersion and strong mixed packing area, and the segregation index representing the mixing effect of the IS-RPB is only 0.003–0.018 as evaluated by the iodide–iodate system . The macroscopic flow pattern in the IS-RPB is close to that of plug flow, and liquid backmixing can be neglected .…”
Section: Introductionmentioning
confidence: 99%